Measuring Corporate Social Responsibility in Sport Industry: Development and Validation of Measurement Scale - Amir Montazeri; Mahdi Talebpour; Reza Andam; Anoshirvan Kazemnejad (The Society of Aging and Physical Activity (SAPA), 2017)
Background. While more and more sport organizations broadly acknowledge their ability at delivering social values, corporate social responsibility (CSR) is rapidly growing at a significant rate across the professional sport industry and its related organizations. Despite the growing body of research in this area, measuring CSR is still problematic. Objectives. Therefore, the aim of this study is to provide an efficient, valid, and reliable measure of CSR reflecting the responsibilities of sport industry. Methods. Based on a proposed conceptual framework of CSR, a scale was developed via a standard procedure for developing instrument measures. In this study, to determine and assess the underlying factorial structure, convergent and discriminate validity of measurement scale, exploratory and confirmatory factor analysis was performed. Data was collected from 640 sport fans in Iran's Football Premier League. Results. The results of the analysis provided a five-dimensional structure of CSR in sport, such as economic, philanthropic, ethical, legal, and environmental issues. These dimensions explained 50.827% of the total variance. In addition, the KMO measure was computed and the results indicated an index of 0.927. Moreover, the values of Cronbach's alpha obtained for five factors ranged from 0.848 to 0.967. The results show the reliability and validity of this new scale in sport industry. Conclusion. This study implies that from a consumer's perspective, CSR is perceived as a set of attributes; therefore, it is important for a professional sports team's management to understand fans' interest in social issues and fans' responses to various CSR programs.